The effect of cervical mobilization on joint position sense, balance and gait in patients with multiple sclerosis: a randomized crossover study - Maden, Tuba; Bayramlar, Kezban; Tuncer, Ayşenur (Taylor and Francis Ltd., 2024)
Objective: To investigate the effect of cervical mobilization on joint position sense, balance and gait in multiple sclerosis (MS) patients. Methods: Sixteen MS patients received traditional rehabilitation and traditional rehabilitation+cervical mobilization treatments in different orders, 2 days a week for 4 weeks. For the cervical mobilization, joint traction and shifts with myofascial release techniques were applied. Joint position sense was evaluated from the bilateral knee and ankle joints with a digital goniometer, balanced with the Berg Balance Test (BBT), the Functional Reach Test, and gait with the Dynamic Gait Index (DGI) and the Timed 25-Foot Walk Test. Results: Improvements were determined in joint position sense, balance, gait with both treatment methods (p < 0.05). With the addition of cervical mobilization to traditional treatment, there was observed to be an increased effect carried over in knee joint position sense and BBT (p < 0.05). The BBT and DGI scores improved in the group applied with cervical mobilization following the washout period (p < 0.05). Conclusions: Cervical mobilization could be effective in improving joint position sense, balance and gait, and accelerated improvements in a short time. The application of cervical mobilization could be a supportive treatment method to improve position sense, balance and gait in patients with MS. © 2024 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: cervical region; manual therapy; Multiple sclerosis; postural control; proprioception